Progressive shear band propagation in metallic glasses under compression. (1st June 2015) - Qu, R.T.; Liu, Z.Q.; Wang, G.; Zhang, Z.F.
Abstract: Shear band plays a key role in dominating the strength and plasticity of metallic glasses, and exhibits two kinds of propagation modes under compression, i.e., progressive and simultaneous propagation. These two different propagation modes of shear bands lie in different stages of plastic deformation. Prior to macroscopic yielding, shear bands have already been initiated yet not penetrated through the sample. These inserting shear bands exhibit linearly decreasing plastic strain from the end to tip, demonstrating a progressive propagation mode. Once the macroscopic yielding occurs, the major shear band fully transects the sample and propagates in a simultaneous sliding manner. The progressive propagation of shear bands causes an apparent work-hardening behavior, which can be well explained by assuming a higher critical stress for shear band initiation than propagation. The results demonstrate that metallic glasses with a smaller difference between critical conditions for initiation and propagation of shear band should have better plastic deformability, which can be reflected by the plastic strain to macroscopic yielding read from stress–strain curves.